Perceiving Customer Preferences in Product Innovation of Fashion Startup using Blue Ocean Strategy - Livia Supranata; Tony Antonio (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to investigate the creation of product innovation towards fashion start-up business by applying Blue Ocean Strategy. This study explores customers’ preferences towards fashion product as the basis of fashion product innovation. Furthermore, customers’ preferences also works as the basis for adjustment to the company’s value offered to the market. This research uses a descriptive qualitative approach where informants are determined using a combination of snowball sampling and purposive sampling technique with 9 informants, consisting of 5 consumers, 2 competitors, and 2 fashion experts. The research object is Elvier, a fashion start-up brand with evening wear products. The data collection method in this research is done using semi-structured interviews and documentation. Finally, Source triangulation is used to gain validity and reliability for this research. The research finds that design, quality and price were found to be the key drivers for customers’ purchasing decision. Furthermore, brand identity also plays an important role that influences customers’ consideration. Several hidden pain points were also discovered which are used to help creating product innovation that fits the customers’ needs. Perceiving customer’s preferences is practically needed to develop and design innovative product. Blue Ocean Strategy is not only help to map where the company could be, based on customer’s preferences and needs, but also to reveal customer’s hidden pain points as considerations to creatively solve customer’s problem by innovating new product.